Ajaran Paulus Tentang Kebangkitan Orang Percaya Dalam I Korintus 15 : 1 – 58 - Bert Haniko (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2022)
The way of the cross is for the Lord Jesus Christ to atone for human sins. This is clearly the expression “Christ died for our sins” (I Cor. 15:3). Next Paul emphasizes His resurrection on the third day (v. 4).This explanation gives an understanding that the cross and the resurrection of Jesus Christ cannot be separated from one another. Both are part of God's great act with the goal of human salvation. Morris (1994: 116) quotes Walther Kunneth's view as follows: Jesus' death provided atonement and atonement, the